Telehealth for Ophthalmic Nursing Care (Teleopthamology) Patient Due to Covid-19 - Wibawa, Shinta; Aulawi, Khudazi (Alta Dharma Publisher, 2022)
Background: A large number of users of Telehealth by health workers for eye care of patients to minimize contact with patients during the Covid-19 pandemic. Objective: This scoping review discussed the application of teleophthalmology in the care of eye patients during the Covid-19 pandemic. Methods: This study followed the acronym PCC (P = population; C = concept; C = context). Journals were obtained through the Pubmed, Science Direct, Clinical Key, and Medline databases. Result: A total of 220 findings appeared, then narrowed by the limitation of the last 10 years in the year of publication, full-text article / open access, using English, type of article was a research article, related to Telehealth for eye care patients due to covid-19. After investigating the same paper, it was checked based on inclusion criteria, and finally, six journals were synthesized. Discussion: The method used in Teleopthalmlogy was A distinction between asynchronous and synchronous, for example, video visits and smartphones. Conclusion: Teleophthalmology was effective and efficient when used during the Covid 19 pandemic. Recommendation: It can be used for the initial assessment of patients to reduce the number of patient visits to health facilities, for example, hospitals